O letramento social da Comunidade Indígena Tapeba e o ensino de Língua portuguesa na Escola Indígena Índios Tapeba. - Forte, Ana Cristina (2024)
This dissertation aims to analyze the pedagogical material (textbooks) for teaching the Portuguese language at the Escola Indígena Índios Tapeba, with regard to the social literacies of the community in question. The choice for the school is justified because it is the pioneer in indigenous school education in the state of Ceará, as well as a reference in cultural and social engagement for other indigenous schools of the Tapeba ethnic group. As theoretical foundations, the study is based on sociointeractionism, which sees language as essentially a social act through which people interact. Theoretical studies also include concepts of literacy, teaching the Portuguese language and aspects of indigenous education. Given the nature of the study, from a methodological point of view, the research is qualitative in nature, given the focus on understanding the complexities between the social and cultural aspects that involve this investigation. In general, the research is divided into four main stages: contextualization of the school, as well as Portuguese language teaching and social literacy in the community; conducting interviews, using questionnaires, with the community; description of the structure and activities of the Portuguese language textbook and corpus analysis. The results obtained reveal that this school is a space for maintaining Tapeba culture and ancestry. In relation to the analysis of textbooks and the literacy of the community, it is understood that there are similarities and differences, taking into account the specificities of these people.